THE IMPORTANCE OF EFFECTIVE SCHOOL LEADERSHIP - NDLOVU, BY FRANCIS (IJRDO- Journal of Educational Research, 2017)
The aim of this paper is to provide the rationale for policymakers to invest in school leadershippolicy. It describes the importance of school leadership and the major challenges faced byschool leaders. Effective school leadership is essential to improve teaching and learning withineach school and to connect the individual school to the outside world. And yet school leadersacross all countries are facing challenges which policymakers need to address. In recent years,the workload of school leaders has expanded and intensified as a result of increased schoolautonomy and accountability for learning outcomes. As the expectations of what schools shouldachieve have changed dramatically, schools are seeking to develop new forms of leadershipbetter suited to respond to the needs of rapidly evolving societies. This involves enhancing thecapacity of current leaders and preparing and training future leaders.